Zonisamide add-on in tremor-dominant Parkinson's disease- A randomized controlled clinical trial. (December 2022) - Pillai, Kanchana Soman; Bhat, Priyanka; Srivastava, Achal Kumar; Rajan, Roopa; Radhakrishnan, Divya M.; Elavarasi, Arunmozhimaran; Srivastava, MV Padma; Singh, Mamta Bhushan; Vishnu, V.Y.; Prasad, Kameshwar; Pandit, Awadh Kishor; Goyal, Vinay
Abstract: Introduction: and objective: Tremor is a disabling symptom of PD that usually responds poorly to available standard pharmacological agents. This study aimed to assess the effect of Zonisamide 25 mg on tremor in tremor-dominant PD patients as compared to placebo. Methods: This was a randomized, placebo-controlled, double-blind study. Parkinson's disease patients were allocated either to the intervention group (standard treatment along with Zonisamide 25 mg add-on) or the placebo group (standard treatment along with placebo). Baseline Unified Parkinson's Disease Rating Scale (UPDRS) and Tremor Research Group Essential Tremor Rating Scale (TETRAS) scores, as well as accelerometric tremor analysis were done and follow-up assessments of the same were done after 12 weeks of intervention. Percentage change from baseline in the UPDRS tremor score was the primary outcome whereas percentage change from baseline of total UPDRS score, UPDRS rigidity and bradykinesia scores, TETRAS score, and accelerometric tremor analysis values were the secondary outcomes. Results: There was no significant difference in the percentage change from baseline UPDRS tremor scores between the two groups (placebo: 8.33 [-19.89–23.86] vs drug: 26.14 [-35.58 to −16.07], p-value: 0.164, CI: 0.157–0.171). Best-case analysis for missing values showed a significant improvement in the drug group, compared to the placebo group (p-value: < 0.001, CI: <0.001 - <0.001). Conclusion: Zonisamide at a dose of 25 mg per day did not improve tremor in tremor-dominant PD patients, however, a positive trend was seen as compared to Placebo in the UPDRS tremor score. Larger studies are required to confirm this finding. Highlights: No significant improvement in tremor with Zonisamide compared to placebo. There was a trend for greater improvement in tremor compared to placebo. A best-case analysis showed a significant difference between the groups. Greater improvement in total UPDRS and TETRAS score compared to placebo was found. This study showed a safe adverse effect profile with a low dose of Zonisamide.